Islamic spirituality development and ethical workplace conduct: conceptual paper - Abd Rahman, Ismail; Hashim, Junaidah; Abdul Latif, Faridah (Association of Global Management Studies, 2014)
Many organisations are conducting trainings for their employees to improve their work skills and development. However, trainings on developing their spiritual aspect are being emphasised. Several studies have shown that spirituality in the workplace could increase work behaviour and moral values. This paper reviews Islamic spirituality development programmes in Malaysia, as well as workplace ethical conduct based on Islamic perspective. This paper proposes a conceptual model showing the relationships between Islamic spirituality development programmes, akhlaq, and workplace ethical conduct by reviewing the theory of human capital, human resource development, and human resource development from Islamic perspective. This paper also reviews existing literature on spirituality at workplace and workplace ethical conduct. The study might contribute towards enhancing the field of human resource development, specifically in the aspect spirituality development.